Pengembangan Literasi Budaya Melalui Permainan Tradisional Congklak Di Era Digital Bagi Anak Usia Dini - Purnamasari, Eka; Sefriyanti, Sefriyanti (Jurnal Ilmiah POTENSIA, 2025)
This study aims to analyze the traditional game of congklak on cultural literacy and character development of early childhood students in the digital era. The research method uses descriptive qualitative. The subjects of this study were one class B teacher and 20 children aged 5-6 years. Data collection through direct observation, in-depth interviews with teachers, and student participation in congklak game sessions to obtain a holistic picture. Data analysis techniques using Three triangulation techniques, namely source triangulation, technique triangulation, and time triangulation, were used to assess the validity of the research data. The results of the study showed that the traditional game of congklak can develop students' cognitive, affective, and psychomotor skills and can develop cooperation and honesty. In addition, students' learning motivation and understanding of local cultural heritage are increasingly developing. The traditional game of congklak has succeeded in integrating holistic character education and strengthening national cultural identity in the school curriculum.